1995
DOI: 10.1093/carcin/16.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of heterocyclic aromatic amines catalyzed by human arylamine N-acetyltransferase isozymes (NAT1 and NAT2) expressed in Salmonella typhimurium

Abstract: Heterocyclic aromatic amines formed during the cooking of meat and meat-derived products can be activated to reactive metabolites which bind to DNA, induce mutations and cause tumors in animals. A principal route of metabolic activation is N-oxidation to hydroxylamines, and their subsequent activation by acetyltransferase-catalyzed O-acetylation. We have used mutagenicity assays to study O-acetylation of heterocyclic arylhydroxylamines by the two isozymes of human N-acetyltransferase, NAT1 and NAT2, expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…51 Josephy and coworkers have shown that mutagenic activation of PhIP in Salmonella is not promoted by hNAT2, but MeIQx genotoxcity is linked to hNAT2 activation. 53 These docking results are not consistent with this result because both molecules are able to bind in the active site of hNAT2.…”
Section: Heterocyclic Amine Dockingmentioning
confidence: 83%
“…51 Josephy and coworkers have shown that mutagenic activation of PhIP in Salmonella is not promoted by hNAT2, but MeIQx genotoxcity is linked to hNAT2 activation. 53 These docking results are not consistent with this result because both molecules are able to bind in the active site of hNAT2.…”
Section: Heterocyclic Amine Dockingmentioning
confidence: 83%
“…Metabolic activation of MeIQx by extrahepatic cytochrome P450 isoforms, such as cytochrome P4501A1 (CYP1A1), has also been reported (13). N-hydroxyMeIQx can be further O-acetylated by N-acetyltransferase 2 (NAT2) to the acetoxy derivative that is highly unstable, leading to electrophilic intermediates that are mutagenic (14) and form DNA adducts (15).…”
Section: Introductionmentioning
confidence: 99%
“…Purpurin is one of several hydroxyanthraquinone constituents found in madder root (Kawasaki et al, 1992), extracts of which are used both as herbal remedies for bladder and kidney stones (Gebhardt, 1979) and as food colorings. Previously, we have demonstrated that purpurin is protective against a number of food-derived heterocyclic amines in bacterial mutagenicity assays (Marczylo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other NIntroduction hydroxylated heterocyclic amines, acetylation of Trp-P-2(NHOH) does not increase the mutagenicity (Nagao et al, The cooking of meat and fish forms bacterial mutagens 1983; Saito et al, 1983a;Wild et al, 1995;Marczylo et al, (Sugimura, 1982), which have been identified as rodent carcino-1999). Purpurin inhibits Trp-P-2(NHOH) mutagenicity to the gens (Sugimura, 1985) and are suspected human carcinogens same extent in TA98 and O-acetyltransferase-deficient TA98- (Weisburger, 1993;Adamson et al, 1995;Schut and 1,8-DNP 6 (Marczylo et al, 1999).…”
mentioning
confidence: 99%